Youtube Stories: the Webseries - Finocchi, Riccardo (E|C, 2020)
The web series are a widespread phenomenon of audiovisual production. However, a precise semiotic analysis of such phenomenon is still missing. This article analyses the web series by trying to study how they produce sense. In this context, the article will describe how a series of audiovisual texts, which are uploaded on Youtube, could gain textual coherence and consistency. A generative semiotic analysis of some recurring elements in the narrative organization of the web series will be also proposed.